Perancangan Game untuk Menumbuhkan Kebanggaan terhadap Indonesia bagi Generasi Muda Indonesia - Faikar Izzani; Agung Eko Budiwaspada; Dudy Wiyancoko (Wimba : Jurnal Komunikasi Visual, 2013)
Indonesia has the potential to become a respected developed nation, but until now it is still riddled with many problems. The pride of Indonesians to their country must be restored to motivate them to contribute to the nation. The media that will be used is mobile game with targeted segment Indonesian middle-class youth aged 15-21 years old. Research method used are observation, literature study, and interview with related parties. The content that will be used are native or acquired Indonesian technology and innovations. This is important because those are the base of a nation's development. Those contents are developed using captology and game designtheories. Basic brief of the designed game are 2D Visuals and using emergent gameplay. Interview with purposive sampling method to the target segment showed that they expect items consumed to be well designed and have significant values embedded. The game will be titled "Bangun Indonesia!", it has three in-game elements that players can explore its relationship with each others. Those three are Solusi, Potensi, and Masalah. The element that can be manipulated directly by the players is Solusi. It will interact with Potensi or Masalah with the purpose of neutralizing Masalah or strengthtening Potensi. The assumptions of game's operational and user's responses are players acquired information about Indonesian technologies and innovations, creative experience by playing game, ability to measure their knowledge, and enlightenment about the potential of Indonesian technologies and innovations in solving the nation's problems.Development potentials for the game are leveling concept, player-updating concept with curatorship scheme, multiplayer concept, strenghtening it's cognitive concept, and analogizing player with government officials.Marketing models for this game areGeneric, Sponsorship, and Policy models. With all of those concepts, Bangun Indonesia! game is expected to develop its player's national pride, and inspiring them to contribute in developing Indonesia.